PRODUCTION OF DH-PLANTS IN CULTURE OF ISOLATED MICROSPORE IN CARROT - T. S. Vjurtts; E. A. Domblides; N. A. Shmykova; M. I. Fedorova; L. Ju. Kan; A. S. Domblides (Овощи России, 2018)
The main goals of the research were to study the factors affecting on the process of embryogenesis in culture of isolated microspores, optimize the existing protocols, and finally produce the doubled haploid plants in carrot (DH-plants). Out of 10 carrot accessions tested in 2017 the embyoids were obtained in 8 carrot accessions with the use of 5 different media. The highest yield of embyoids was obtained in accessions 7kt (84 embryoids per Petri dish). It was shown that       optimal                explants              were     buds      containing microspores at late vacuolated uninucleate stage. The first divisions in microspores were seen in 3 days of cultivation. After 40 days, the welldeveloped embryoids can be observed by naked eye. It was also shown that further cultivation of these embryoids on medium with 13% agarose over 60 days provoked the active secondary embryoid formation. Owing to this, it is recommended to place the embryoids at heart-shaped stages on another regeneration medium supplied with 2 % of agarose, enabling to register correctly the number of well-formed embryoids. We carried out the study on influence of such factors as genotype and composition of medium, and their combination on embryoid formation in 8 genotypes on 5 various media. ANOVA analysis showed that the plant genotype was the main factor causing the embryoid formation, whereas the effect of both factors had an impact on the number of embryoids developed. The counting the chromosome number in meristem cells and also observation of chloroplast number in stoma guard cells enabled to reveal that most of the plants produced were the doubled haploids